Adoptive T cell therapy of solid tumors: time to team up with immunogenic chemo/radiotherapy. (February 2022) - Pocaterra, Arianna; Catucci, Marco; Mondino, Anna
Highlights: Solid tumors represent the vast majority of newly diagnosed cancer, and yet only 50% of immuno-oncology trials are directed to them. Several barriers limit efficacy of Adoptive T cell therapy, including poor infiltration and local immunosuppressive mechanisms. Chemo-modulatory and radiotherapy exert immune-modulatory functions, including Immunogenic Cell Death, opening the way to combined strategies. Local deposition of cytokines can tune tumor infiltration and promote an inflammatory environment. Preclinical data indicate that combinatorial strategies unleash ACT therapeutic efficacy leading to antigen spreading and protective immunity. Abstract : Adoptive T cell therapy (ACT) with tumor-reactive lymphocytes can overcome the immune desert of poorly immunogenic tumors and instruct tumor eradication. Several hurdles limit the efficacy of this strategy against solid tumor including, but not limited to, sub optimal T cell engraftment, tumor infiltration, poor tumor antigenicity/immunogenicity, and immunosuppressive or resistance mechanisms. Recent advances indicate that concomitant treatments can be set in place to offset such barriers. In this review, we highlight the beneficial effects of combining ACT with conventional chemo and/or radiotherapy. While originally classified as immunosuppressive, these methodologies can also promote the engraftment of ACT products, immunogenic cell death, and the reprogramming of more favorable microenvironments. Data indicates that systemic and local chemo/radiotherapy regimens promote intratumoral cytokine and chemokine upregulation, tumor antigen presentation and cross presentation, infiltration and in situ T cells reactivation. Here we review the most recent contributions supporting these notions and discuss further developments.